Stability and Volumetric Properties of Asphalt Mixture Containing Waste Plastic - Abd Kader, S.A. (EDP Sciences, 2017)
The objectives of this study are to determine the optimum bitumen content (OBC) for every percentage added of waste plastics in asphalt mixtures and to investigate the stability properties of the asphalt mixtures containing waste plastic. Marshall stability and flow values along with density, air voids in total mix, voids in mineral aggregate, and voids filled with bitumen were determined to obtain OBC at different percentages of waste plastic, i.e., 4, 6, 8, and 10 by weight of bitumen as additive. Results showed that the OBC for the plastic-modified asphalt mixtures at 4, 6, 8, and 10 are 4.98, 5.44, 5.48, and 5.14, respectively. On the other hand, the controlled specimen's shows better volumetric properties compared to plastic mixes. However, 4 additional of waste plastic indicated better stability than controlled specimen. © The Authors, published by EDP Sciences, 2017.